Carrier position third and fifth order IMDs of a radio-over-fibre system laser - Yong, Lisa; Mohamad, Kadim Suhaidi; Awangku Abdul Rahman, Pgn. Hj. Yusof (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/